1988
DOI: 10.2307/281217
|View full text |Cite
|
Sign up to set email alerts
|

Ohio Hopewell Trophy-Skull Artifacts as Evidence for Competition in Middle Woodland Societies Circa 50 B.C.. A.D. 350

Abstract: During the Middle Woodland period in eastern North America, modified human skulls are interjected into a broader pattern of "trophy"-artifact manufacture. Interpretations of these human trophies have resulted in a polarity of opinion-that they are the remains of (1) revered ancestors, or (2) defeated enemies. Both previous investigations of the problem support exclusively the "revered-ancestor" interpretation. Results of the present study, which makes use of a six-site Ohio Hopewell sample and stylistic and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…A warfare explanation is further supported by the demographic patterns and burial practices of the trophy victims. These individuals were predominantly young adult males-the same demographic group that typically engages in warfare activities (Seeman, 1988;Redmond, 1994). Even so, women and old adults were not spared from trophy-taking and dismemberment practices, which suggests a form of reciprocal violence involving the social substitution of noncombatant individuals (Kelly, 2000;Mensforth, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A warfare explanation is further supported by the demographic patterns and burial practices of the trophy victims. These individuals were predominantly young adult males-the same demographic group that typically engages in warfare activities (Seeman, 1988;Redmond, 1994). Even so, women and old adults were not spared from trophy-taking and dismemberment practices, which suggests a form of reciprocal violence involving the social substitution of noncombatant individuals (Kelly, 2000;Mensforth, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Dismembering warfare victims and preserving their body parts as trophies has occurred for thousands of years (Keeley, 1996;Walker, 2000) and throughout the world (e.g., Bennike, 1985;Smith, 1993Smith, , 1997Hoskins, 1996;Frayer, 1997;Mensforth, 2001;Williams et al, 2001;Verano, 2003;Kellner, 2006;Chacon and Dye, 2007a;Finucane, 2008;Tung, 2008). Trophy-taking and dismemberment were common warfare practices for indigenous groups throughout pre-Columbian North America (Ewers, 1967;Seeman, 1988;Willey, 1990;Owsley, 1994;Milner, 1995Milner, , 1998Leblanc, 1999;Kuckelman et al, 2002;Chacon and Dye, 2007a). Both practices included the intentional removal of body parts, with one major difference-trophy-taking retained the body part for later display (Gifford, 1955), while dismemberment left the body part in the burial pit with the victim (Willey, 1990;Mensforth, 2001).…”
mentioning
confidence: 99%
“…Seeman's (1988) study of possible trophy skulls suggested that warfare may have episodically characterized political relations. Alternatively, relations within Hopewellian society have been portrayed as generally nonviolent (Carr 2006), owing to the relative absence of trauma on Hopewellian skeletons, a hypothesis supported by skeletal analysis (Johnston 2002;Milner 1995).…”
Section: Sociopolitical Organizationmentioning
confidence: 98%
“…Trophy body parts were often taken after battle as tokens of a warrior's bravery (Allen et al, 1985;Seeman, 1988;Owsley, 1994), for ceremonial purposes (Zegwaard, 1959;Powell, 1977), or to provide protection from the dead enemy's spirit (Proulx, 1971;Owsley & Berryman, 1975). The most common form of trophytaking was scalping, identified by a characteristic pattern of cut marks which encircle the crown of the head, usually beginning at the forehead, going over the ears, and across the back of the skull (Allen et al, 1985;Smith, 1993;Olsen & Shipman, 1994).…”
Section: Trophy Takingmentioning
confidence: 99%
“…Human skeletal remains can be modified into artifacts by cutting, carving, drilling, polishing, and decoration with metal or stones. Such artifacts may be ornamental (Dixon, 1959;Williams, 1975;Jamieson, 1983), play a part in mortuary rituals (Baby, 1961), be included with burials (Hester, 1969;Hohmann et al, 1985), or serve as trophies (Proulx, 1971;Seeman, 1988;Ravesloot & Spoerl, 1989;Simon, 1992;. Trophy skulls are characterized by holes drilled through the top or bottom for attachment of a handle, and may be polished, carved, or decorated with paint, copper, or shell (Proulx, 1971;Ravesloot & Spoerl, 1989;Seeman, 1988;Pijoan et al, 1989;Owsley et al, 1994).…”
Section: Ritual Artifact Productionmentioning
confidence: 99%